OzoNews Volume XX - 30 January 2020 - United Nations Environment Programme (2020)
In this issue: 1. Kigali Amendment latest ratifications 2. FACTSHEET: Proposed additional HS code sub-headings for HFCs in advance of the 2022 HS code update - Cheat Sheet 3. FACTSHEET: Dealing with seized ODS - Options for Article 5 countries 4. UNEP OzonAction Training Programme for National Ozone Officer 5. Substantial twentieth-century Arctic warming caused by ozone-depleting substances 6. Increase in global emissions of HFC-23 despite near-total expected reductions 7. Quantitative detection of iodine in the stratosphere 8. Botswana introduces fees for permits of ODS 9. Fiji urged to adopt and ratify Kigali Amendment 10. New Zealand - Methyl bromide update January 2020 11. Berkeley plans to phase out “ozone-depleting” refrigerant over next ten years 12. Egypt ozone protection program: A review of the activities 13. EC fraud office makes illegal F-gas imports a priority 14. Kyrgyzstan Parliament approved ratification of the Montreal Protocol amendments 15. Armenia to forbid production of substances that contribute to the destruction of the ozone layer 16. QinetiQ to build ozone-monitoring satellite for European Space Agency